ETHICAL ISSUES IN ACCOUNTING PRACTICES AND THEIR IMPLICATIONS TO GREEN WASHING - Pamungkas, Eko Wiji; Surahman, Bambang; Patria, Nelly (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aims to analyze ethical issues in accounting practices and their implications for greenwashing in corporate sustainability reporting. The research employs a qualitative approach using the literature review method by examining various academic journals, books, research reports, and sustainability reporting frameworks related to accounting ethics and environmental disclosure. The findings indicate that unethical accounting practices, such as selective disclosure, manipulation of sustainability information, exaggeration of environmental achievements, and omission of environmental liabilities, significantly contribute to greenwashing practices. The study also reveals that market competition, stakeholder pressure, weak corporate governance, and insufficient regulatory oversight encourage companies to prioritize symbolic legitimacy over substantive environmental accountability. Furthermore, greenwashing negatively affects stakeholder trust, corporate reputation, investment decisions, and the credibility of sustainability reporting systems. The research highlights the importance of ethical leadership, transparent reporting practices, independent verification, and strong governance mechanisms in minimizing greenwashing risks. This study concludes that ethical accounting practices play a crucial role in ensuring transparency, accountability, and organizational sustainability. Strengthening ethical standards in accounting is therefore essential for improving the reliability of environmental disclosures and supporting sustainable business practices.